Frequency and release flux of calcium sparks in rat cardiac myocytes: a relation to RYR gating - Zahradníková, Alexandra (The Rockefeller University Press, 2010)
Cytosolic calcium concentration in resting cardiac myocytes locally fluctuates as a result of spontaneous microscopic Ca(2+) releases or abruptly rises as a result of an external trigger. These processes, observed as calcium sparks, are fundamental for proper function of cardiac muscle. In this study, we analyze how the characteristics of spontaneous and triggered calcium sparks are related to cardiac ryanodine receptor (RYR) gating. We show that the frequency of spontaneous sparks and the probability distribution of calcium release flux quanta of triggered sparks correspond quantitatively to predictions of an allosteric homotetrameric model of RYR gating. This model includes competitive binding of Ca(2+) and Mg(2+) ions to the RYR activation sites and allosteric interaction between divalent ion binding and channel opening. It turns out that at rest, RYRs are almost fully occupied by Mg(2+). Therefore, spontaneous sparks are most frequently evoked by random openings of the highly populated but rarely opening Mg(4)RYR and CaMg(3)RYR forms, whereas triggered sparks are most frequently evoked by random openings of the less populated but much more readily opening Ca(2)Mg(2)RYR and Ca(3)MgRYR forms. In both the spontaneous and the triggered sparks, only a small fraction of RYRs in the calcium release unit manages to open during the spark because of the limited rate of Mg(2+) unbinding. This mechanism clarifies the unexpectedly low calcium release flux during elementary release events and unifies the theory of calcium signaling in resting and contracting cardiac myocytes.